Tingkat Kepuasan Pasien Pemegang Jaminan Kesehatan Nasional (JKN) Terhadap Pelayanan Kefarmasian di Instalasi Farmasi Rawat Jalan Rumah Sakit Umum Daerah Sayang Kabupaten Cianjur: Level of Satisfaction of National Health Insurance (JKN) Holders Patients with Pharmaceutical Services in the Outpatient Pharmacy Installation of Sayang Regional General Hospital, Cianjur District - Ananda Putri Fatimatuzzahra; Oci Etri Nursanty; Imam Syafi’i (UIMA Press, 2024)
Hospital pharmacy services should prioritize patient safety, based on a new paradigm of patient care where pharmacy officers play a role, focusing not only on the drug but also on the patient. One of the good qualities of pharmaceutical services can be seen in patient satisfaction. The purpose of this study was to determine the level of patient satisfaction of National Health Assurance Holders (JKN) towards Pharmaceutical Services in Outpatient Pharmacy Installation of Regional General Hospital Sayang District, Cianjur, using 5 dimensions of service quality, namely Reliability, Responsiveness, Assurance, Empathy (Emphaty), and Tangible (Tangible). This study used descriptive research design with quantitative approach, sampling technique in this study was carried out with purposive sampling technique i.e. sampling technique with certain considerations, selected respondents were patients with National Health Insurance (JKN), patients who were able to communicate, write, read well, in addition to having been treated at least twice so that they were responsive in giving answers. The number of respondents in this study was 100. The instruments used in this study are questionnaires that have been tested for validity and reliability. The results of this study were percentage values on Reliability (66.6%), Responsiveness (64.5%), Assurance (68%), Empathy (63.6%), Tangible (61.2%) at 61.2% and percentage value of all dimensions at 64.78%. The conclusion of this study is to show that patients with National Health Assurance (JKN) are satisfied with pharmacy services at the Outpatient Pharmacy Installation of Sayang Regional General Hospital, Cianjur Regency.